2016
DOI: 10.1073/pnas.1611023114
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic receptor-dependent chemokine receptor 2 expression regulates leukocyte recruitment to the heart following acute injury

Abstract: Following cardiac injury, early immune cell responses are essential for initiating cardiac remodeling and tissue repair. We previously demonstrated the importance of β2-adrenergic receptors (β2ARs) in the regulation of immune cell localization following acute cardiac injury, with deficient leukocyte infiltration into the damaged heart. The purpose of this study was to investigate the mechanism by which immune cell-expressed β2ARs regulate leukocyte recruitment to the heart following acute cardiac injury. Chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 40 publications
4
49
0
Order By: Relevance
“…Although initial infarct sizes post-I/R were not different among Ccr2 -/or Cx3cr1 -/mice or strain-matched wild-type controls (not shown), Ccr2 deficiency significantly improved cardiac function after I/R (Fig. 3h), consistent with previous reports 31,48,49 . Moreover, cell therapy by MNC injection in mice lacking Ccr2 imparted no further functional benefit, given the already enhanced state of cardiac healing after I/R (Fig.3h).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Although initial infarct sizes post-I/R were not different among Ccr2 -/or Cx3cr1 -/mice or strain-matched wild-type controls (not shown), Ccr2 deficiency significantly improved cardiac function after I/R (Fig. 3h), consistent with previous reports 31,48,49 . Moreover, cell therapy by MNC injection in mice lacking Ccr2 imparted no further functional benefit, given the already enhanced state of cardiac healing after I/R (Fig.3h).…”
supporting
confidence: 91%
“…Moreover, cell therapy by MNC injection in mice lacking Ccr2 imparted no further functional benefit, given the already enhanced state of cardiac healing after I/R (Fig.3h). Loss of Ccr2 showed a reduction in overall CD68 + cell content in the post-I/R heart with or without cell therapy, consistent with prior studies demonstrating that targeting circulating CCR2 + monocytes/macrophages can reduce inflammation in the heart 31,49 . By comparison, Cx3cr1 null mice lacking tissue resident macrophage activity showed left ventricular dysfunction after I/R injury that was similar to wild-type controls, but these mice no longer benefitted from MNC therapy and showed a much greater total inflammatory response ( Fig.…”
supporting
confidence: 86%
“…Beta blocker infusion alters splenic leukocyte parameters over time in vivo. Our previous studies identified key molecular changes in leukocytes in response to hematopoietic cell-specific deletion of β 2 -AR, including increased splenic VCAM-1 expression and leukocyte retention, as well as decreased leukocyte CCR2 expression in BM-derived leukocytes (14,15). Therefore, we aimed to determine whether prior treatment with β 2 -ARselective or clinically used beta blockers would similarly alter these leukocyte parameters.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we previously developed chimeric mice lacking β 2 -AR expression in cells of hematopoietic origin via transplantation of β 2 -AR-knockout (β 2 -AR-KO) bone marrow (BM) into wild-type (WT, C57BL/6J) recipient mice and subjected them to MI. Strikingly, these chimeric mice displayed severe changes in several leukocyte parameters, including increased splenic vascular cell adhesion molecule 1 (VCAM-1) expression and leukocyte retention, as well as decreased bone marrow cell (BMC) expression of chemokine receptor 2 (CCR2) and leukocyte recruitment to the heart after injury (14,15). Collectively, these genetic studies suggested that because Following injury, leukocytes are released from hematopoietic organs and migrate to the site of damage to regulate tissue inflammation and repair; however, leukocytes lacking β 2 -adrenergic receptor (β 2 -AR) expression have marked impairments in these processes.…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that some of the protective effects of certain established therapeutic approaches in patients with MI, such as angiotensin converting enzyme inhibition (Leuschner et al, ), angiotensin receptor blockade (Kohno et al, ), mineralocorticoid receptor (MR) inhibition (Fraccarollo et al, ), β‐adrenoceptor blockade (Garcia‐Prieto et al, ) and administration of statins (Zhang et al, ), may involve direct modulation of inflammation. For example, leukocyte‐specific β 2 ‐adrenoceptor signalling has been reported to mediate leukocyte recruitment in the infarcted heart (Grisanti et al, ), and a recent study suggested that the infarct‐limiting effects of β‐blockade with metoprolol in a mouse model of MI were lost following neutrophil depletion or through genetic knockdown of genes associated with platelet:neutrophil interactions (Garcia‐Prieto et al, ). However, considering the broad effects of neurohumoral pathways on both cardiomyocyte and non‐cardiomyocyte populations, the relative contribution of inflammatory cell modulation remains unclear.…”
Section: The Rationale For Targeting Inflammation After MImentioning
confidence: 99%